Improved Fractional Subequation Method and Exact Solutions to Fractional Partial Differential Equations. (17th May 2020) - Jiang, Jun; Feng, Yuqiang; Li, Shougui
Abstract : In this paper, the improved fractional subequation method is applied to establish the exact solutions for some nonlinear fractional partial differential equations. Solutions to the generalized time fractional biological population model, the generalized time fractional compound KdV-Burgers equation, the space-time fractional regularized long-wave equation, and the (3 + 1 )-space-time fractional Zakharov-Kuznetsov equation are obtained, respectively.